The building activities in ‘Bracara Augusta’. The building process of a city: the agents and the craftsmen - Ribeiro, Jorge Manuel Pinto; Martins, Maria Manuela (Romanitas - Revista de Estudos Grecolatinos, 2015)
Bracara Augusta's builders and artisans took on an important role in the city's economy. Form a group of individuals complex and diverse, often invisible in written sources, whose activity we recover through Archeology. The city experienced, from a very early age, and throughout its history, a growing role, characterized by important administrative and religious functions. This gradual political growth was accompanied by a significant and permanent constructive activity, whose analysis takes us to the universe of the economy, the social world of work, innovation and fashions. In this article, we will try to identify the various trades behind this dynamism, frequently denounced by the structures and materials they produced, appreciated and / or acquired.
Keywords: Bracara Augusta; Society; Economy; Constructive agents; Materials